FREE WILL REIMAGINED - Sweet, Emily (The Oracle, 2021)
God is omniscient, omnibenevolent and omnipotent, which means he is all-knowing, all-good, and all-powerful, respectively. A common objection to the existence of God is the existence of evil, because it implies that God is not all-good. However, the problem of evil can be explained by his desire for humans to be free moral agents. This paper will discuss how free will justifies the existence of evil and how this kind of free will can occur alongside a limitless God. These points will be understood by examining Immanuel Kant’s views on moral freedom, J. L. Mackie’s objections, Richard Swinburne’s defense of free will, John Hick’s arguments about divine guidance, and how these theories relate to modern monotheistic religions.